Analysis of Community Structure of Plankton as Bioindikator of Water Quality in Cikapundung River, West Java - Nugraha, Fauzi Ahmad Ghiffary; Fitriyah, Ita; Supriyatna, Ateng; MA, Rahmat Taufik (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2024)
The Cikapundung River is a sub-river of the Citarum River that is heavily polluted with waste. The presence of waste in the Cikapundung River can cause various environmental problems. Research on plankton community structure analysis needs to be conducted in the Cikapundung River to determine community structure, its relationship with physical and chemical parameters, and water quality conditions. This research was conducted in May-June 2023 using a purposive sampling method at 3 stations with different characteristics. Sampling was done 3 times in each station with an interval of 1 week. The parameters of COD, BOD, Nitrate, and Phosphate were tested at the sampling location and LPKL PDAM. Plankton sampling was done by filtering 6L of water into a plankton net and preserved using 70% alcohol. Plankton identification was carried out at the Integrated Laboratory of UIN Sunan Gunung Djati based on morphological characteristics under a microscope observation. Data on physical and chemical parameters obtained were analyzed using IBM SPSS software version 25.0.0. Then continued with the Spearmann correlation test between physical and chemical parameters and plankton communities. The results showed that there were 46 genus of plankton in Cikapundung River.The highest diversity and evenness values were found at station 3 with mean values of 1.847 and 0.618. The highest dominance value is found at station 1 with a mean value of 0.381. The mean values of the probity index SI and TSI in Cikapundung River are 0.419 and 0.425. There is no real correlation between physical and chemical parameters in the plankton community. The probity index indicates that the Cikapundung River belongs to the β/α mesosaprobic water group with a moderate level of pollution.